N22 Audit into initial response to vedolizumab infusions for IBD. (25th January 2019) - Lloyd-Ford, G; Gordon, M
Abstract: Background: Vedolizumab is a humanised IgG1 monoclonal antibody, aimed at reducing GI inflammation, (NICE 2015). This audit will look at the average time patients start to see improvements in their symptoms following commencement of Vedolizumab. According to NICE (2015), the majority of patients are expected to respond within 6–12 weeks. Methods: The Ambulatory Unit currently infuses 39 patients with Vedolizumab. Forty-nine per cent ( n = 19), are male with and 51% ( n = 20) are women. Forty-six per cent ( n = 18) with Crohns Disease (CD) and 54% ( n = 21) with ulcerative colitis (UC). All patient who attended where asked to fill out a short questionnaire in relation to how quickly they had seen an improvement in their symptoms, in particular, fatigue, loose stools, pain and rectal bleeding. They were asked to give an idea on a weekly timescale as to how quickly those aspects of the disease had resolved. Questionnaire where given out on the Ambulatory Unit and patients made aware that their responses would not alter their treatment. As this an audit that does not require patient-specific information to be included, no ethical approval was required. Results: Comparing Crohns to ulcerative colitis, the significant findings were as follows. Fatigue was not a significant factor for 33% ( n = 6) of the CD patients and 9% ( n = 2) of the UC patients, however for those for whom it was a concern, 66% ( n = 12) of the CD and 80% ( n = 17) of the UC patients reporting improvement after Week 8. Loose stools was resolved in 66% ( n = 12) of the CD patients by Week 8, however 11% ( n = 2) stated it was not a factor in their disease. When looking at UC, 33% ( n = 7) found symptoms reduced at Week 8, 38% ( n = 8) stated reducing in symptoms after Week 8 and 9% ( n = 2) stated they did not suffer from loose stools. From a pain perspective 66% ( n = 12) of the CD patients experience relief my Week 8, whereas 54% ( n = 12) of the UC patients found relief after Week 12. The final aspect looked at was rectal bleeding, 61% ( n = 11) of the CD patients stated this was not a symptom of their disease as oppose to it being a after for all bar 1 of those with UC. For those who did experience rectal bleeding of those with CD, 27% ( n = 5) found a response by Week 8 whereas of those with UC 52% ( n = 11) found relief after Week 8. Conclusions: The results suggest the complexity of inflammatory bowel disease both in terms of management and patient experience. The majority of CD patients had resolved most of their symptoms by 8 weeks, however the UC patients in particular in relation to fatigue, pain and rectal bleeding did not gain a good response until after 8 weeks. However the CD group was smaller than the UC group presented here which could alter the results presented, with that in mind a bigger cohort study over a longer period may prove useful.